“Come, Let Us Prostrate and Bow Down”: The Importance of Embodied Worship in The Psalter - Melak Tsegaw (Jurnal Koinonia, 2022)
Biblical worship is the response of created beings to the self-revelation of the Creator, and a proper response in worship engages both mind and body—the whole person. A closer study of the worship theme in the Psalter elucidates its physical dimension and the relevance of engaging the body in worshiping the Lord. This paper explores the importance of embodied worship as it is purported in the Psalter. First, the connection between biblical anthropology and worship is established. Arguments are presented from the book of Psalms to show how and why the physical aspect of human nature receives attention. Second, the study elucidates practical implications that can foster a deeper biblical worship experience. In particular, the processional movements studied in the book of Psalms teach us the proper attitude worshipers should nurture when they approach God in worship. The act of prostration expresses gratitude and ascribes honor to the Lord. Also, standing posture can instill a sense of commitment to consecrate ourselves to God.